Effect of Delay on Selection Dynamics in Long-Term Sphere Culture of Cancer Stem Cells - Peng Tang; Aijun Fan; Jianquan Li; Jun Jiang; Kaifa Wang (Discrete Dynamics in Nature and Society)
To quantitatively study the effect of delay on selection dynamics in long-term sphere culture of cancer stem cells (CSCs), a selection dynamic model with time delay is proposed. Theoretical results show that the ubiquitous time delay in cell proliferation may be one of the important factors to induce fluctuation, and numerical simulations indicate that the proposed selection dynamical model with time delay can provide a better fitting effect for the experiment of a long-term sphere culture of CSCs. Thus, it is valuable to consider the delay effect in the future study on the dynamics of nongenetic heterogeneity of clonal cell populations.